Analisis Faktor-Faktor Struktur Modal dan Nilai Perusahaan - Amin Wijoyo, Henny Wirianata, (Jurnal Ekonomi, 2020)
Regression test results show only profitability affects the capital structure, while liquidity, growth, and size, do not affect. Profitability, size, and capital structure affect firm value, while liquidity and growth do not affect.Â  Research on the capital structure and firm value was conducted in the manufacturing industry listed in IDX from 2016 to 2018. Data samples are taken using purposive random sampling and then processed with Eviews 10. Moderation test results indicate that the capital structure is a mediator of the effect of profitability on firm value, but cannot be a mediator for the influence of other variables on firm value of manufacturing industry companies listed in IDX 2016 through 2018.